Kredit Usaha Rakyat, Dana Penguatan Modal, dan Modal Sendiri terhadap Peningkatan Pendapatan UMKM di Kabupaten Sleman - Nabila Dian Utami; Avininda Dewi Nindiasari (ISAS, 2026)
This study aims to analyze the influence of People's Business Credit, Capital Strengthening Funds, and Equity on increasing MSME income in Sleman Regency. This study used a quantitative method with purposive sampling, involving 100 business actors spread across 17 sub-districts in Sleman Regency. Data were collected through questionnaires and analyzed using multiple linear regression tests using the SPSS application. The results show that Small and Medium Enterprise Credit has a positive and significant effect on increasing MSME income, with a regression coefficient of 0,262 and a significance level of 0,048. Capital Strengthening Funds also have a positive and significant effect, with a regression coefficient of 0,286 and a significance level of 0,025. Furthermore, equity capital has a positive and significant effect on increasing MSME income, with a regression coefficient of 0,229 and a significance level of 0,031. This indicates that capital utilization, both from internal and external sources, can increase business capacity, maintain operational stability, and strengthen the competitiveness of Micro, Small, and Medium Enterprises. Keywords: People's Business Credit, Capital Strengthening Fund, Own Capital, MSME Income